Embracing Complexities: Transformations of International Student Mobility amid Global Turmoil - Shchepetylnykova, Liz; Kaya-Kaşıkcı, Sevgi (International Higher Education, 2025)
<h3 id="although-scholarship-on-international-student-mobility-ism-is-extensive-the-evolving-landscape-of-ism-with-increasingly-diverse-rationales-actors-and-modalities-requires-new-data-and-forms-of-understanding-this-article-reflects-on-the-new-developments-in-ism-in-the-context-of-postpandemic-and-geopolitical-turmoil-we-conclude-by-urging-scholars-to-engage-in-critical-examination-of-the-dominant-theories-and-concepts-informing-our-understanding-of-mobility" data-pm-slice="1 1 []">Although scholarship on international student mobility (ISM) is extensive, the evolving landscape of ISM, with increasingly diverse rationales, actors, and modalities, requires new data and forms of understanding. This article reflects on the new developments in ISM in the context of postpandemic and geopolitical turmoil. We conclude by urging scholars to engage in critical examination of the dominant theories and concepts informing our understanding of mobility.